Fostering academic hospitality: Addressing the needs of muslim postgraduate students in Canadian higher education - Mohamed, Derrick Rasheed; George, Imbenzi (Journal of International Students, 2025)
Muslim postgraduate students in Canada face unique challenges that intersect with their cultural, academic, and religious identities. This study examines survey responses from 524 students at a Canadian university, 19.5% of whom identified as Muslim, to explore their experiences and key obstacles. Findings reveal significant challenges, including adapting to Canadian academic norms, navigating cultural integration, financial stress, and balancing religious observances within a secular academic environment. This research highlights the critical role of academic hospitality in addressing these barriers. Strategies such as culturally sensitive faculty training, inclusive orientation programs, and institutional policies tailored to religious and cultural diversity are shown to enhance students’ academic success and sense of belonging. This study contributes to the growing discourse on equity and inclusion in higher education, offering practical recommendations for fostering supportive environments for Muslim international students in Canadian post-secondary institutions.